Turkish adaptation of the undergraduate nursing clinical evaluation form: a validity and reliability study - Arkan, Burcu; Pehlivan, Seda; Yılmaz, Dilek; Vatansever, Nursel (The European Research Journal, 2021)
Objectives: The study was conducted for the purpose of determining the validity and reliability of the “Undergraduate Nursing Clinical Evaluation Form (CEF)” in a Turkish sample. Methods: One hundred sixty-seven students enrolled in Faculty of Health Sciences Department of Nursing participated in the study. Study data were collected via the Student Description Form and CEF. The Cronbach's α internal consistency coefficient was calculated for the reliability of the total scale. Pearson correlation analysis was used to determine the correlation between items and total scores. Results: In the validity of the scale, CFA was used to investigate the consistency of the scale with the original scale. When the fit indices of the model tested using CFA were examined, it was seen that the chi-square value was significant. When the Cronbach's α reliability coefficients were examined, the reliability of the form was found to be quite good in terms of domains and total score. The correlations between the items and total scale score ranged between 0.42 and 0.77. Cronbach's α coefficient was greater than 0.90 for each item. Conclusions: Undergraduate Nursing Clinical Evaluation Form is a valid and reliable tool that can be used in the Turkish culture.